Evaluación del sistema de riego por aspersión de cultivo de piña (ananas comosus) en Banacol, sección Finca Sardinal, Puntarenas - Abarca-Monge, Sianny Patricia (Instituto Tecnológico de Costa Rica, 2017)
This paper’s central theme was the evaluation of the sprinkler irrigation system, to determine the overall efficiency of the hydraulic network, because in the past years the company has presented a decrease in the quality of the fruit regarding size and weight. The project was developed in the company Banacol, in Finca Sardinal, which main’s activity is pineapple exportation. Its administrative location corresponds to District 02 Pitahaya that belongs to Canton 01 Puntarenas. The farm has 475 hectares of crops, with diverse parts of land in different phenological stages (sowing, development of the crop, half of season and harvest), both in first and second harvests. The plantation is supplied with water for irrigation through a pumping station, located near the Guacimal River. Laboratory tests were carried out to determine the texture, apparent specific weight, water constants such as field capacity and permanent wilting point, infiltration and hydraulic conductivity. Also, field tests to evaluate the uniformity of application and the state of the components of the hydraulic network. It was determined that the irrigation time used is not suitable to restore the water lost by evapotranspiration of the crops, also, that the minimum sheet is applied so that the crop survives, which affects the quality of the pineapple. In addition, the application of water that the system has is deficient for the crop, low values were presented in the coefficient of uniformity and uniformity of distribution. Some factors that affect the performance are the system components ‘bad maintenance, not using the pressure regulators in the irrigation canyons and the incidence of the wind.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2017.
Keywords: Evaluación; Riesgo por aspersión; Eficiencia; Riego; Cultivo